2020
DOI: 10.1002/hep.31228
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiome‐Macrophage Crosstalk Contributes to Cholestatic Liver Disease by Promoting Intestinal Permeability in Mice

Abstract: BaCKgRoUND aND aIMS: Mounting evidence supports an association between cholestatic liver disease and changes in the composition of the microbiome. Still, the role of the microbiome in the pathogenesis of this condition remains largely undefined. appRoaCH aND ReSUltS: To address this, we have used two experimental models, administering alpha-naphtylisocyanate or feeding a 0.1% 3,5-diethoxycarbonyl-1,4-dihydrocollidine diet, to induce cholestatic liver disease in germ-free mice and germ-free mice conventionalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 50 publications
3
58
0
3
Order By: Relevance
“…Mechanistically, in murine models of ALD, lower abundances of Firmicutes and higher abundances of Verrucomicrobia and Bacteroidetes were observed when compared with those in healthy mice [ 64 ]; the dysbiotic microbiome contributed to the progression of liver disease via the promotion of intestinal inflammation and the resulting reduction in tight junction protein expression, which was similar to our findings in murine models of cholestasis [ 65 ]. Depletion of antimicrobial molecules was also demonstrated in murine models of ALD [ 64 , 66 ].…”
Section: The Intestinal Microbiome and Progression To Hccsupporting
confidence: 85%
See 1 more Smart Citation
“…Mechanistically, in murine models of ALD, lower abundances of Firmicutes and higher abundances of Verrucomicrobia and Bacteroidetes were observed when compared with those in healthy mice [ 64 ]; the dysbiotic microbiome contributed to the progression of liver disease via the promotion of intestinal inflammation and the resulting reduction in tight junction protein expression, which was similar to our findings in murine models of cholestasis [ 65 ]. Depletion of antimicrobial molecules was also demonstrated in murine models of ALD [ 64 , 66 ].…”
Section: The Intestinal Microbiome and Progression To Hccsupporting
confidence: 85%
“…Likewise, our knowledge of the mechanisms mediating both the detrimental and the beneficial effects of different bacteria on liver function and disease progression remain scarce. These may include the capacity of specific bacteria to regulate tight junctions and, thus, intestinal permeability [ 65 ], controlling inflammation [ 66 ], or via the direct effects of bacteria-derived metabolites (e.g., phenylacetic acid) on the liver, as it was observed in obese steatotic patients [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…113,114 KC depletion by CLDN or treatment with an NLRP3 inhibitor significantly attenuates αnaphtylisocyanate (ANIT)-induced cholestatic liver injury, further supporting a role for macrophage inflammasome activation in the pathogenesis of the disease. 115 Studies investigating whether bile acids play an important role in triggering macrophage inflammasome activation have yielded controversial findings. The hydrophobic bile acids chenodeoxycholic acid and deoxycholic acid have been found to induce macrophage NLRP3 inflammasome activation.…”
Section: Hepatic Macrophages In Liver Diseasesmentioning
confidence: 99%
“…A previous study reported that ANIT and DDC treatment could cause intestinal permeability, leading to the translocation of bacteria or their products (LPS) from the leaky intestine into the liver [14] . Additionally, whilst murine experimental models may not fully represent human disease, ANIT and feeding with 0.1% DDC are well-accepted models of sclerosing cholangitis relevant to PSC [27,28] .…”
Section: Tec Alleviated Anit-induced and Ddc-induced Experimental Intrahepatic Cholestasismentioning
confidence: 99%
“…Macrophages, which are composed of resident tissue macrophages and monocyte-derived recruited cells, can differentiate into either classically activated macrophages (a pro-inflammatory phenotype, also called M1 polarity) or alternatively activated macrophages (M2 polarity) which express anti-inflammatory cytokines [13] . Recent studies have demonstrated that the intestinal microbiome leads to the process of cholestasis-mediated cell death and inflammation by activating the mechanisms of the inflammasome in macrophages [14] . Additionally, clinical studies have suggested that in cholestasis patients, the recruitment of monocytes and macrophages in diseased liver is significantly increased [15] .…”
Section: Introductionmentioning
confidence: 99%